Strategi Komunikasi Inovasi Hasil Riset Pada Masyarakat Lingkar Kampus IPB University - Rahmawati, Ismi Arsilah; Muljono, Pudji; Matindas, Krishnarini; Kurniawati, Kamilah Dwi (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
IPB university is one of the universities that has many innovations, this can be shown by IPB's achievements for 12 (twelve) consecutive years (2008-2019) participating in the 100 plus Indonesian innovation program organized by the Business Innovation Center (BIC) with support from the Ministry of Education, Culture, Research and Technology (Kemenristekdikti RI) and The Indonesian Academy of Sciences (LIPI). Higher education is an innovation center that plays a role in the progress of society, providing impact and solutions from the results of research conducted. However, the reality is whether the research carried out provides an effective solution to the community or is it just a collection of books that are neatly stored in the library and can only be accessed by certain circles. The research method is designed using qualitative method. Qualitative data informants are representatives of each component, managers and innovators. Qualitative data processing using SWOT analysis (Strength, Weakness, Oppurtunities, Threats). The results showed the current situation has opportunities and strengths so that it can take advantage of internal strengths and existing opportunities, therefore the recommended strategy in this study is an aggressive strategy Keywords: Innovation research result, IPB University, SWOT analysis